Phytofabrication of Silver nanoparticles: Novel Drug to overcome hepatocellular ailments. (2018) - Singh, Asha; Dar, Mohd Yaqoob; Joshi, Beenu; Sharma, Bhawna; Shrivastava, Sadhana; Shukla, Sangeeta
Graphical abstract: Highlights: AgNPs were prepared by biological method using Morus alba leaf extract. AgNPs unveiled in vitro antiproliferative effects against HepG2 cell lines. AgNPs exhibited strong antioxidant activities and hepatoprotective effects. Act as drug delivery carriers and curing agents against hepatocellular ailments. Abstract: This study aimed to treat hepatocellular ailments with biologically prepared silver nanoparticle (AgNPs). AgNPs were formulated using Morus alba leaf extract and their synthesis and characterization were determined by UV–visible spectroscopy, Transmission Electron Microscope (TEM), Scanning Electron microscope (SEM), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR) and Zeta analysis. In vitro studies on HepG2 cell lines for cytotoxic effect and in vivo studies in a rat model for hepatoprotective effect were carried out using biologically prepared AgNPs as curing agents. Dose response cytotoxicity on hepatic cancer (HepG2) cells was confirmed by 3-(4, 5-dimethyl thiazole-2-yl)-2, 5-diphenyl tetrazolium (MTT) assay. The inhibitory concentrations (IC50 ) were found to be 20 μg/mL and 80 μg/mL for AgNPs and M. alba leaf extract respectively against HepG2 cells at 24 h incubation. In addition, hepatotoxicity in Wistar rats (180 ± 10 g) was induced by intraperitoneal injection of N -nitrosodiethylamine (NDEA) and were treated with different doses of AgNPs (25, 50, 100 μg/kg). NDEA administration showed a significant rise in the biochemical parameters whereas the levels of enzymic antioxidants were decreased. Obtained results revealed that the elevated levels of Liver Function Test (LFTs) biomarkers were significantly reversed and the antioxidant levels were significantly recouped towards normal after the conjoint treatment of AgNPs in a dose-dependent manner. Thus green synthesized AgNPs showed a promising curing effect on hepatocellular ailments.